Kebijakan Politik Hukum Pada Usaha Mikro, Kecil, dan Menengah (Umkm) Terhadap Perekonomian Indonesia (Studi Kasus: Umkm Di Kota Depok) - Nadapdap, Binton Jhonson; Widiarty, Wiwik Sri; Nadapdap , Binoto (CV. Green Publisher Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of Indonesia’s economy but continue to face structural challenges due to weak legal protection and complex regulations. This study examines the legal politics toward MSMEs and their impact on equitable economic development, focusing on a case study in Depok City and a comparison with Yogyakarta Special Region (DIY). The research applies juridical-normative and juridical-empirical approaches through regulatory analysis and interviews with MSME actors and local officials. The findings reveal that MSME policies in Depok remain partial, as no specific local regulation exists despite the issuance of Mayor Regulation No. 15/2021. Conversely, DIY has implemented a more comprehensive framework through Regional Regulation No. 6/2022 and Governor Regulation No. 58/2023, covering empowerment, fiscal incentives, and legal protection. At the national level, Government Regulation No. 47/2024 on MSME Bad Debt Write-Off serves as a breakthrough in improving credit access. The study recommends a distributive justice–based legal reform (Rawls) and stronger central–local policy synergy to build an inclusive and sustainable MSME ecosystem.